2017
DOI: 10.24911/ijmdc.1.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Saudi board residents: comparison between Family Medicine and Internal Medicine

Abstract: Background: Many previous studies reported high burnout rates among medical professionals in different fields, from students and nurses to surgeons, specialists and consultants. The current study was performed to compare the prevalence of burnout in family medicine and internal medicine residents and to reveal the risk predictors of high burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These observations find resonance in studies focusing on FM residents in the KSA. [ 13 24 ] Our findings can be attributed to the specialisation of our study group. Demanding specialties like anaesthesia, emergency medicine and surgery often report high emotional exhaustion and cynicism.…”
Section: Discussionmentioning
confidence: 84%
“…These observations find resonance in studies focusing on FM residents in the KSA. [ 13 24 ] Our findings can be attributed to the specialisation of our study group. Demanding specialties like anaesthesia, emergency medicine and surgery often report high emotional exhaustion and cynicism.…”
Section: Discussionmentioning
confidence: 84%
“…Close to a third of respondents reported having high EE, whereas one-fifth of respondents reported having high DP (cynicism), and a sizeable minority of healthcare workers reported having low personal accomplishment (high burnout). [17] Another study revealed that during the COVID-19 pandemic, there was a considerably high incidence of burnout among healthcare workers. Sociodemographic, occupational, economic, and exposure characteristics showed significant correlations with higher degrees of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2024_____________________42 This present study revealed that the prevalence of burnout syndrome among healthcare professionals in Saudi Arabia is comparable to findings in earlier research conducted there. [17,18] The global prevalence of this syndrome among healthcare professionals is one in three. This study revealed that the prevalence of BOS among healthcare workers in Saudi Arabia is greater than the global prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Alfaleh (2017) found high levels of emotional exhaustion, depersonalization, and personal achievement burnout among family medicine and internal medicine residents. [ 21 ] Among 2,509 residents belonging to a cohort of graduating family medicine residents in the United States, 36.8% met the burnout criteria. [ 22 ] Another study conducted in the United States in 2018 found that medical residents and fellows had a high prevalence of burnout, with around 60% of respondents reporting symptoms of burnout.…”
Section: Discussionmentioning
confidence: 99%